Formulation and Sunscreen Activity Test of Lotion of Buas-Buas (Premna Serratifolia Linn.) Leaf Extract - Adahane, Euistya Febrianti Putri; Isnindar, Isnindar; Luliana, Sri (Majalah Obat Tradisional, 2024)
Excessive UV exposure can cause various skin disorders, so protection from UV rays is needed by using sunscreen. One of the plants that have the potential as a sunscreen is buas-buas leaf (Premna serratifolia Linn.) which contains flavonoid compounds. Sunscreen formulated in lotion form is the most common preparation found in the market. The purpose of this study was to evaluate the physical characteristics of lotion preparations and to determine the potential of lotion of buas-buas leaf extract as a sunscreen. Buas-buas leaf extract was obtained through maceration extraction with 96% ethanol solvent. Lotion with the active substance of buas-buas leaf extract was made with concentration variations of 1, 2, and 3%. Evaluation of the physical characteristics of the lotion was tested with organoleptic observation parameters, homogeneity, pH, spreadability, and adhesion. Then, it was tested for sunscreen potential using UV-Vis spectrophotometry. Data were analyzed with SPSS Statistics 22 software, namely the One Way ANOVA (Analysis of Variance) test. The results of the study were the three lotion formulas of buas-buas leaf extract met all the requirements of the physical characteristics evaluation test. The SPF value of F1 (1%) is 7.12 (extra protection), F2 (2%) is 9.54 (maximum protection) and F3 (3%) is 15.68 (ultra protection). Based on the results of the study, it can be concluded that the lotion of buas-buas leaf extract meets the requirements of evaluating the physical characteristics of lotions and has activity as a sunscreen.